Review of state-of-the-art and conceptual framework approaches in seaside port operations: berth allocation, and quay crane assignment and scheduling - Maria Boluda-Prieto; Ana Esteso; M.M.E.; Angel Ortiz (International Journal of Production Management and Engineering, 2025)
The continuous growth in the volume of goods transported by sea has led to a significant increase in the number of vessels and containers arriving at ports, requiring more efficient management of vessel loading and unloading operations. These operations involve three key problems: berth allocation, quay crane assignment, and quay crane scheduling. In response to these challenges, numerous mathematical programming models have been proposed, and various literature reviews analysing these models have emerged in recent years. However, the abundance of such reviews highlights the need for a systematic organisation of available information to consolidate the state of the art in this field. To this end, this paper conducts a systematic literature review, following PRISMA guidelines, based on publications retrieved from Scopus and Web of Science. This study focuses specifically on existing state-of-the-art studies that analyse mathematical models for berth allocation, quay crane assignment, and/or quay crane scheduling. The objectives of this work are threefold: (i) to assess the scope of previous literature reviews, including their purpose, the problems addressed, and their temporal coverage; (ii) to identify and group the dimensions they use to categorize the problems and the models designed to address them; and (iii) to compile the future research directions proposed in these reviews and highlight those that remain relevant. The findings provide a comprehensive overview of trends, highlight research gaps, and propose dimensional groups to consider when developing more holistic decision support frameworks for port operations.